Akreditasi Satuan PAUD Berbasis Sistem Penilaian Akreditasi (SISPENA) - Febriani, Eliza; Warmansyah, Jhoni (UIN Imam Bonjol Padang, 2021)
PAUD accreditation is a tangible form of assessing the feasibility of the quality of the program run by the PAUD unit. This study aims to examine various literatures on the accreditation of PAUD units based on Sispena 3.1. The research method used is literature review, researchers collect data from various literatures to solve a problem. The results of the study obtained are (1) in attaching the assessment process documents in accordance with the Accreditation Prerequisite Assessment (PPA) instrument through SISPENA 3.1; (2) the assessor conducts an assessment process for the classification of applications for accreditation (KPA); (3) Education units in fulfilling the PPA can be assisted by the integration of an external database with the Sispena 3.1 application; (4) The data collection procedure for Sispena 3.1 starts from the PPA filling stage to the Validation and Verification stage to determine the accreditation results